Exploring Digital Entrepreneurship: A Qualitative Study on New Business Models and Digital Marketing Strategies - Razak, Nurlaely; Syamsu, Nur; Djunaid, Muhammad Rusli; Tenriolle, A. (Manunggal Halim Jaya, 2024)
This qualitative study explores the dynamics of digital entrepreneurship and marketing, aiming to provide insights into the multifaceted nature of the digital economy. Employing a systematic literature review and thematic analysis methodology, the research delves into the role of platform-based business models, digital marketing strategies, and emerging trends within the digital landscape. The study reveals that platform ecosystems play a pivotal role in driving value creation and innovation, serving as catalysts for entrepreneurship by providing essential infrastructure and opportunities for value exchange. Additionally, it emphasizes the significance of data-driven decision-making and marketing analytics in optimizing digital marketing strategies, enabling businesses to deliver personalized experiences and drive engagement across multiple channels. Key findings include the transformative implications of platform-based business models for various stakeholders, the importance of user-centric design principles in enhancing customer experiences, and the challenges posed by regulatory compliance and technological integration. The study contributes to theoretical understanding by elucidating the complexities of digital entrepreneurship and marketing, while also offering practical implications for entrepreneurs to navigate the competitive digital marketplace successfully.